Brochs and the empire : the impact of Rome on Iron Age Scotland as seen in the Leckie Broch excavations - MacKie, Euan Wallace (Archaeopress, 2016)
Excavations of the Leckie Iron Age broch in Stirlingshire, Scotland, reflect the expansion of the Roman Empire into southern Scotland in the late first century AD.